USING QUESTION ANSWER RELATIONSHIP STRATEGY TO IMPROVE READING COMPREHENSION - Nadia, Hafizhatun (English Department of Faculty of Tarbiyah and Teacher Training, 2014)
This study based on the English Department students of the second semester of STAIN Palangka Raya problems in Reading Comprehension. This study was interested in overcoming the problems by applying a particular strategy in the teaching-learning process to help the students comprehend texts better. The strategy proposed in this study is Question Answer Relationship (QAR) Strategy. The research subjects in this study were 36 students. In this study, the researcher used Classroom Action Research (CAR) as research design. The data in this study were collected from test, and field note. It was found that there was an improvement in the students? ability in Reading Comprehension after Question Answer Relationship (QAR) strategy was applied. The preliminary study result showed that the average score of the students was 60.77. In the first cycle the students? average score developed to 69.99 and it developed to 77.80 in the second cycle. Related to preliminary study, only 10 (27.78%) of the students who got score ? 70. In the first cycle, there were 19 (52.78%) out of 36 students who got scores ? 70, and in second cycle, there were 32 (88.88%) of the students got score ? 70 which was the minimum standard of criterion of the success. Based on the result of the study above, it was proven that Question Answer Relationship (QAR) strategy can improve the students? reading comprehension skills.